Intra-lenticular lens aspiration in paediatric cases with anterior dislocation of lens - Sahay, Pranita (Eye (Lond), 2019)
PURPOSE: To assess the outcomes of intra-lenticular lens aspiration (ILLA) in paediatric cases with anterior dislocation of lens. METHODS: A retrospective review of medical records of cases with anterior dislocation of the lens in children (age < 16 years) that underwent ILLA between June 2017 and May 2018 was performed. Corrected distance visual acuity (CDVA), intraocular pressure (IOP), and anterior segment findings were noted at presentation and follow-up. Surgical notes were reviewed for all cases. Post-operative central corneal thickness (CCT) and central macular thickness (CMT) were recorded. RESULTS: Eleven eyes of eight patients with a median age of ten years underwent ILLA. There were four males and four females. The median duration of symptoms was 2 months, CDVA was 1.77 logMAR, and IOP was 16 mm of Hg. Ten eyes had corneo-lenticular touch with corneal oedema, and two had raised IOP at presentation. Homocystinuria (n = 2/8), Microspherophakia (n = 2/8), Marfan syndrome (n = 1/8), Buphthalmos (n = 1/8) and Ectopia lentis et pupillae (n = 1/8) were the identifiable causes for anterior dislocation. There were no intra-operative complications in any case. Immediate post-operative corneal oedema and raised IOP was observed in nine and three cases respectively and was treated with medical therapy. The median post-operative CDVA and IOP at 6-months was 1 logMAR and 15 mm of Hg respectively. The median CCT and CMT were 516 and 248 μm respectively. Five eyes developed a central corneal descemet scar. CONCLUSIONS: ILLA is a safe and effective technique for surgical removal of an anteriorly dislocated lens in paediatric cases.